Answer:
1) 2 + 8i
2) -4 + 5i
3) 10 + 15i
4) 19 - 9i
5) 5
Explanation:
The operations with imaginary numbers are equal to those of the real numbers considering i as a variable, but with a property that allows to simplify the expression more, that is that i squared equals -1. Taking this property into account, we solve the expressions like this:
1) (3 + 2i) - (1-6i) = 3 + 2i - 1 + 6i = 2 + 8i
2) 4i + 3-6 + i-1 = 5i - 4 = -4 + 5i
3) 5i (3-2i) = 5i*3 - 5i*2i = 15i - 10i^2 = 15i - 10(-1) = 15i + 10 = 10 + 15i
4) (5 + 3i) (2-3i) = 5*2 - 5 3i + 3i*2 - 3*3i^2 = 10 - 15i + 6i - 9i^2 = 10 - 9i - 9(-1) = 10 - 9i + 9 = 19 - 9i
5) (2 + i) (2-i) = 2*2 - 2*i + 2*i - i^2 = 4 - 2i + 2i - (-1) = 4 + 1 = 5
Hope this helps!